Record of Aggregation of Alien Tropical Schyphozoan Rhopilema nomadica Galil, 1990 in the Mediterranean Coast of Egypt - Fadel Madkour, Fedekar; Safwat, Walaa; Hassan Hanafy, Mahmoud (International Marine Science Journal, 2019)
Recently, annual swarm of invasive Erythrean schyphozoan RhopilemanomadicaGalil, 1990 appeared along Egyptian Mediterranean coasts causing beach closures and fishing problems. The present study conducted survey and field monitoring on R. nomadica during blooming season in the Egyptian Mediterranean coast throughout three consecutive years (2015-2017). Three main features of R. nomadica bloom were addressed; viz starting date, duration and maximum density of aggregation. In 2015, the bloom started on 28 July, and over the following two years the bloom starting date shifted earlier being 19 July in 2016 and 15 June in 2017. The duration of the bloom varied yearly giving the longest duration in 2017 when the bloom continued in high density for a month. The highest density of R. nomadica was about 896 medusae/1000 m3 in 2017. The medusae diameter ranged between 21 to 112 cm. The average bell diameter for each year displayed gradual increasing values over the years. The consistent annual R. nomadica blooming was attributed to the high level of eutrophication and ecosystem degradation occurred along the Mediterranean coast since last decades. The shifting in the annual bloom starting date and duration may reflect the adaptation of R. nomadica to the climate change effect on the Mediterranean Sea temperature.
Keywords: Rhopilema nomadica; Suez Canal; invasive species; Mediterranean Sea